Chromium-free stainless steel passivator and passivating treatment method

Through the formulation of chromium-free stainless steel passivator and electrophoresis technology, the problem that traditional passivator is difficult to achieve multiple performance improvements is solved, and a passivation film with ideal thickness and excellent comprehensive performance is formed, and environmental pollution is reduced.

CN119800469AInactive Publication Date: 2025-04-11CHONGQING DONGCHUN TECHNOLOGY DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510068356.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional stainless steel passivating agents are difficult to achieve the ideal thickness, excellent corrosion resistance, high hardness, good adhesion and chemical stability of the passivation film at the same time, and the process is complex, the cost is high, and the environmental pollution is serious.

Method used

The chromium-free stainless steel passivator is used, and the formula includes a mixture of urea and inorganic ceramic graphene oxide, a silane coupling agent, iron-doped nanotitanium dioxide, a mixture of molybdenum disulfide and titanium dioxide, polyethylene 2,5-furandicarboxylate, thiosulfate, water-soluble derivatives of alginic acid, hydrogen peroxide and ethanol, and passivation is carried out by electrophoresis technology.

Benefits of technology

The formed passivation film has ideal thickness, excellent corrosion resistance, high hardness, good adhesion and chemical stability, while reducing environmental pollution and making the treatment method simple and easy to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800469A_ABST
    Figure CN119800469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel surface treatment, and discloses a chromium-free stainless steel passivator and a passivating treatment method.The passivator is prepared from, by mass, 5-10 parts of urea and inorganic ceramic graphene oxide mixture; 2-5 parts of a silane coupling agent; 3 to 7 parts of iron doped nano titanium dioxide Fe-TiO2; 2-6 parts of a mixture of molybdenum disulfide and titanium dioxide; 5 to 10 parts of poly (ethylene 2, 5-furandicarboxylate); 2 to 5 parts of thiosulfate; 3-8 parts of a water-soluble derivative of alginic acid; 1-3 parts of hydrogen peroxide; the passivating agent is prepared from the raw materials, the surface of a stainless steel workpiece is cleaned, electrophoresis passivating treatment is conducted, the passivated stainless steel workpiece is washed with deionized water and put into a drying box to be dried, and quality detection is conducted on the stainless steel workpiece subjected to post-treatment. And it is detected that the formed passive film has the advantages of ideal thickness, excellent corrosion resistance, high hardness and good adhesive force and chemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel surface treatment, in particular to a chromium-free stainless steel passivating agent and a passivation treatment method. Background Art

[0002] In the surface treatment of stainless steel parts, traditional passivation agent formulations face technical challenges. These challenges are mainly reflected in the difficulty in achieving the ideal thickness of the passivation film, excellent corrosion resistance, high hardness, good adhesion and chemical stability at the same time. Specifically, when traditional passivators form a passivation film of sufficient thickness, they often sacrifice other key properties of the film layer. For example, increasing the thickness may lead to a decrease in corrosion resistance and adhesion, or reduce chemical stability while increasing hardness. In addition, traditional passivation technology may also face problems such as complex process, high cost and environmental pollution. Therefore, the development of a new passivation agent that can ensure the ideal thickness while giving the stainless steel surface excellent comprehensive properties has become the focus and difficulty of current research. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies in the prior art, the present invention provides a chromium-free stainless steel passivator and a passivation treatment method, wherein the formed passivation film has the advantages of ideal thickness, excellent corrosion resistance, high hardness, good adhesion and chemical stability, thereby solving the problem that traditional passivators are difficult to simultaneously achieve the ideal thickness, excellent corrosion resistance, high hardness, good adhesion and chemical stability of the passivation film.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a chromium-free stainless steel passivator, wherein the raw materials of the passivator are in the following mass parts: 5-10 parts of a mixture of urea and inorganic ceramic graphene oxide; 2-5 parts of a silane coupling agent; 3-7 parts of iron-doped nano-titanium dioxide Fe-TiO2; 2-6 parts of a mixture of molybdenum disulfide and titanium dioxide; 5-10 parts of polyethylene 2,5-furandicarboxylate; 2-5 parts of thiosulfate; 3-8 parts of a water-soluble derivative of alginic acid; 1-3 parts of hydrogen peroxide; and 2-5 parts of ethanol.

[0007] Preferably, the composition ratio of the urea and inorganic ceramic graphene oxide mixture is 3:1.

[0008] Preferably, the composition ratio of the mixture of molybdenum disulfide and titanium dioxide is 2:3.

[0009] Preferably, the raw materials of the passivator are as follows: 6 parts by weight of a mixture of urea and inorganic ceramic graphene oxide; 5 parts by weight of a silane coupling agent; 4 parts by weight of an iron-doped nano-titanium dioxide Fe-TiO2; 5 parts by weight of a mixture of molybdenum disulfide and titanium dioxide; 8 parts by weight of polyethylene 2,5-furandicarboxylate; 4 parts by weight of a thiosulfate; 5 parts by weight of a water-soluble derivative of alginic acid; 2.5 parts by weight of hydrogen peroxide; and 4 parts by weight of ethanol.

[0010] Preferably, the raw materials of the passivator are as follows: 9 parts by weight of a mixture of urea and inorganic ceramic graphene oxide; 3 parts by weight of a silane coupling agent; 6 parts by weight of an iron-doped nano-titanium dioxide Fe-TiO2; 2.8 parts by weight of a mixture of molybdenum disulfide and titanium dioxide; 6.6 parts by weight of polyethylene 2,5-furandicarboxylate; 4.5 parts by weight of thiosulfate; 3.5 parts by weight of a water-soluble derivative of alginic acid; 2.2 parts by weight of hydrogen peroxide; and 4.6 parts by weight of ethanol.

[0011] Preferably, a passivation treatment method of a chromium-free stainless steel passivator is characterized in that the passivation treatment is carried out according to the above-mentioned chromium-free stainless steel passivator, comprising the following passivation treatment steps:

[0012] Step 1: Preparation: preparation of passivating agent and cleaning of the surface of stainless steel workpiece;

[0013] Step 2: Electrophoresis passivation treatment: Using electrophoresis technology, the cleaned stainless steel workpiece is used as the cathode, and the graphite electrode is selected as the inert anode. It is placed in an electrophoresis tank filled with a prepared chromium-free stainless steel passivator, and the electrophoresis parameters are set for passivation;

[0014] Step 3: Post-processing: Take out the passivated stainless steel workpiece, rinse it with deionized water, and put it into a drying oven for drying;

[0015] Step 4: Quality inspection: Conduct quality inspection on the post-processed stainless steel workpieces. The inspection items include the appearance, thickness, corrosion resistance, hardness, adhesion and chemical stability of the passivation film.

[0016] Preferably, the preparation steps of the passivating agent in step 1 are:

[0017] S1.1. Prepare raw materials: prepare a mixture of urea and inorganic ceramic graphene oxide, a silane coupling agent, iron-doped nano-titanium dioxide Fe-TiO2, a mixture of molybdenum disulfide and titanium dioxide, polyethylene 2,5-furandicarboxylate, thiosulfate, a water-soluble derivative of alginic acid, hydrogen peroxide and ethanol in formula weight parts;

[0018] S1.2, mixing: urea and inorganic ceramic graphene oxide mixture, iron-doped nano titanium dioxide Fe-TiO2, molybdenum disulfide and titanium dioxide mixture, polyethylene 2,5-furandicarboxylate, thiosulfate, water-soluble derivatives of alginic acid are added to the reaction container in sequence, and deionized water of 1 / 3 of the total mass of the above raw materials is added at the same time, and the stirrer is turned on and stirred at a speed of 400-450 rpm for 30 to 40 minutes;

[0019] S1.3, dissolving: during the stirring process, add the silane coupling agent along the glass rod, and continue stirring for 20 to 30 minutes to form a stable silane coupling agent modified solution;

[0020] S1.4, adjust pH value: use pH meter to measure pH value of mixed solution, according to pH value measurement result, when pH value is lower than 6, use plastic dropper to add 5% sodium hydroxide solution drop by drop for neutralization; when pH value is higher than 10, use plastic dropper to add 5% dilute hydrochloric acid drop by drop for adjustment, until pH value is stable between 6-10;

[0021] S1.5. Add hydrogen peroxide and ethanol: under stirring, add hydrogen peroxide and ethanol to the mixed solution with adjusted pH value, and continue stirring for 10 to 15 minutes to complete the preparation of the passivating agent.

[0022] Preferably, in the cleaning process of the surface of the stainless steel workpiece in step 1, the stainless steel workpiece is immersed in a pickling solution consisting of nitric acid, sulfuric acid and deionized water in a ratio of 2:1:6 for 15 to 25 minutes.

[0023] Preferably, the electrophoresis parameters in the electrophoresis passivation treatment in step 2 are set as follows:

[0024] S2.1, voltage: controlled between 10-20V;

[0025] S2.2, Temperature: maintained between 20-30℃;

[0026] S2.3, Response time: set to 18-28 minutes;

[0027] S2.4, stirring: during the reaction, magnetic stirring is used for continuous stirring, and the stirring speed is controlled at 50-60 rpm.

[0028] Preferably, the post-processing process in step three is: taking out the passivated stainless steel workpiece, rinsing it with deionized water for 3-7 times to remove the passivation liquid remaining on the surface, and then putting the workpiece into a drying oven and drying it at a temperature of 60-80°C for 45 to 60 minutes.

[0029] Compared with the prior art, the present invention provides a chromium-free stainless steel passivator and a passivation treatment method, which have the following beneficial effects:

[0030] 1. The present invention changes the traditional passivator formula and introduces iron-doped nano titanium dioxide (Fe-TiO2) to replace undoped nano titanium dioxide, which can improve the corrosion resistance of stainless steel parts while improving their hardness. Polyethylene 2,5-furandicarboxylate (PEF), thiosulfate and ethanol are used in combination, which helps to further optimize the chemical stability of stainless steel parts. By adopting electrophoresis technology for passivation treatment, the passivation film formed on the surface of the stainless steel part has an ideal thickness, so that the surface has excellent corrosion resistance, high hardness, good adhesion and chemical stability. In addition, the wastewater generated by the passivator during the passivation process has less environmental pollution, which is specifically manifested in that the chemical oxygen demand (COD), total phosphorus (TP), total nitrogen (TN), ammonia nitrogen (NH3-N), petroleum and heavy metal contents are all low. Therefore, the passivator of the present invention is not only efficient and environmentally friendly, but also the treatment method is simple and easy, and is suitable for the surface treatment of stainless steel parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a flow chart of the passivation treatment using a passivating agent according to the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1 A chromium-free stainless steel passivator, the raw materials of the passivator are in the following mass parts: 5-10 parts of a mixture of urea and inorganic ceramic graphene oxide (GO); 2-5 parts of a silane coupling agent; 3-7 parts of iron-doped nano-titanium dioxide Fe-TiO2; 2-6 parts of a mixture of molybdenum disulfide and titanium dioxide; 5-10 parts of polyethylene 2,5-furandicarboxylate; 2-5 parts of thiosulfate; 3-8 parts of a water-soluble derivative of alginate; 1-3 parts of hydrogen peroxide; and 2-5 parts of ethanol.

[0034] The following table 1 shows the corresponding functions of the raw materials:

[0035] Table 1

[0036]

[0037] Specifically, the composition ratio of the mixture of urea and inorganic ceramic graphene oxide (GO) is 3:1.

[0038] Specifically, the composition ratio of the mixture of molybdenum disulfide and titanium dioxide is 2:3.

[0039] Specifically, a passivation treatment method of a chromium-free stainless steel passivator is performed according to the above-mentioned chromium-free stainless steel passivator, and includes the following passivation treatment steps:

[0040] Step 1: Preparation: preparation of passivating agent and cleaning of the surface of stainless steel workpiece;

[0041] Step 2: Electrophoresis passivation treatment: Using electrophoresis technology, the cleaned stainless steel workpiece is used as the cathode, and the graphite electrode is selected as the inert anode. It is placed in an electrophoresis tank filled with the prepared chromium-free stainless steel passivator, and the electrophoresis parameters are set for passivation. During the passivation process, the passivation solution is properly stirred to ensure that the passivation solution is in full contact with the workpiece surface, so that the passivation reaction is more uniform;

[0042] Step 3: Post-processing: Take out the passivated stainless steel workpiece, rinse it with deionized water, and put it into a drying oven for drying to ensure that the surface of the workpiece is completely dry;

[0043] Step 4: Quality inspection: The post-processed stainless steel workpiece is subjected to quality inspection. The inspection items include the appearance of the passivation film (whether it is uniform, whether there is any leakage), thickness (measured by a film thickness meter), corrosion resistance (tested by salt spray test, etc.), hardness, adhesion and chemical stability, so as to ensure that the passivated workpiece meets the relevant quality standards.

[0044] Specifically, the preparation steps of the passivating agent in step 1 are:

[0045] S1.1. Prepare raw materials: prepare a mixture of urea and inorganic ceramic graphene oxide, a silane coupling agent, iron-doped nano-titanium dioxide Fe-TiO2, a mixture of molybdenum disulfide and titanium dioxide, polyethylene 2,5-furandicarboxylate, thiosulfate, a water-soluble derivative of alginic acid, hydrogen peroxide and ethanol in formula weight parts;

[0046] S1.2, mixing: urea and inorganic ceramic graphene oxide mixture, iron-doped nano titanium dioxide Fe-TiO2, molybdenum disulfide and titanium dioxide mixture, polyethylene 2,5-furandicarboxylate, thiosulfate, water-soluble derivatives of alginic acid are added to the reaction container in sequence, and deionized water of 1 / 3 of the total mass of the above raw materials is added at the same time, the stirrer is turned on, and the mixture is stirred at a speed of 400-450 rpm for 30-40 minutes to fully disperse and dissolve the solid raw materials to form a uniform mixed solution;

[0047] S1.3, dissolving: during the stirring process, add the silane coupling agent along the glass rod, and continue stirring for 20 to 30 minutes to allow the silane coupling agent to fully react with the mixed solution to form a stable silane coupling agent modified solution;

[0048] S1.4, adjust pH value: use pH meter to measure pH value of mixed solution, according to pH value measurement result, when pH value is lower than 6, use plastic dropper to add 5% sodium hydroxide solution drop by drop for neutralization; when pH value is higher than 10, use plastic dropper to add 5% dilute hydrochloric acid drop by drop for adjustment, until pH value is stable between 6-10;

[0049] S1.5. Add hydrogen peroxide and ethanol: Under stirring, add hydrogen peroxide and ethanol to the mixed solution with adjusted pH value, and continue stirring for 10 to 15 minutes to make the hydrogen peroxide and ethanol evenly dispersed in the solution, thus completing the preparation of the passivating agent.

[0050] Specifically, in step 1, the surface cleaning process of the stainless steel workpiece is as follows: the stainless steel workpiece is immersed in a pickling solution composed of nitric acid, sulfuric acid and deionized water in a ratio of 2:1:6 for 15 to 25 minutes to remove the surface oxide layer and impurities. This step is also called activation treatment, and its purpose is to make the stainless steel surface more susceptible to reaction with the passivation solution.

[0051] Specifically, the electrophoresis parameters in the electrophoresis passivation treatment in step 2 are set as follows:

[0052] S2.1, Voltage: Controlled between 10-20V. Lower voltage can make the passivation film more uniform and delicate, avoiding defects such as pinholes in the film layer caused by excessive voltage;

[0053] S2.2, Temperature: Maintained between 20-30℃, this temperature range is conducive to the activity of each component in the passivator, while ensuring the stability of the electrophoresis process and reducing the impact of temperature fluctuations on the quality of the passivation film;

[0054] S2.3, Reaction time: set to 18-28 minutes, which can ensure that the passivation film is fully formed, but will not affect the performance due to excessive thickness of the film layer due to too long a time;

[0055] S2.4, stirring: during the reaction, magnetic stirring is used for uninterrupted stirring, and the stirring speed is controlled at 50-60 rpm. Continuous stirring can evenly distribute the ions in the passivation solution, avoid local concentration differences, ensure that the passivation solution is in full contact with the workpiece surface, and make the passivation reaction more uniform.

[0056] Specifically, the post-processing process in step three is: take out the passivated stainless steel workpiece, rinse it with deionized water 3-7 times to remove the passivation liquid remaining on the surface, and then put the workpiece into a drying oven and dry it at a temperature of 60-80°C for 45 to 60 minutes.

[0057] Example 1

[0058] Specifically, the raw materials of the passivator are as follows: 6 parts of a mixture of urea and inorganic ceramic graphene oxide (GO); 5 parts of a silane coupling agent; 4 parts of iron-doped nano-titanium dioxide Fe-TiO2; 5 parts of a mixture of molybdenum disulfide and titanium dioxide; 8 parts of polyethylene 2,5-furandicarboxylate; 4 parts of thiosulfate; 5 parts of a water-soluble derivative of alginic acid; 2.5 parts of hydrogen peroxide; and 4 parts of ethanol.

[0059] Comparative Example 1

[0060] Specifically, the raw materials of the passivator are as follows: 6 parts by weight of a mixture of urea and inorganic ceramic graphene oxide (GO); 5 parts by weight of a silane coupling agent; 4 parts by weight of undoped titanium dioxide (TiO2); 5 parts by weight of a mixture of molybdenum disulfide and titanium dioxide; 8 parts by weight of polyethylene 2,5-furandicarboxylate; 4 parts by weight of potassium dichromate; 5 parts by weight of a water-soluble derivative of alginic acid; 2.5 parts by weight of hydrogen peroxide; and 4 parts by weight of ethanol (replacing the thiosulfate in Example 1 with potassium dichromate, and replacing the iron-doped nano-titanium dioxide with undoped titanium dioxide (TiO2)).

[0061] The passivating agents prepared in Example 1 and Comparative Example 1 were subjected to passivation treatment, and the results are shown in Table 2 below:

[0062] Table 2

[0063]

[0064] From the analysis of Table 2, we can get:

[0065] Appearance of the passivation film: The passivation films of Example 1 and Comparative Example 1 are uniform and free of plating leakage, indicating that both formulations can form good passivation films.

[0066] Thickness: The thickness of the passivation film of Example 1 is 1.2 μm, and the thickness of the passivation film of Comparative Example 1 is 1.0 μm. The film thickness of Example 1 is slightly thicker, indicating that the mass ratio of the raw materials can provide better protection;

[0067] Corrosion resistance: Example 1 showed better corrosion resistance in the salt spray test, with no obvious corrosion for 1000 hours, while Comparative Example 1 showed slight corrosion after 800 hours, indicating that thiosulfate can improve the corrosion resistance of the stainless steel surface, while potassium dichromate in Comparative Example 1 is not conducive to increasing the corrosion resistance of the stainless steel surface;

[0068] Hardness: The hardness of Example 1 is 55HRC, and the hardness of Comparative Example 1 is 50HRC. The hardness of Example 1 is higher, indicating that iron-doped nano-titanium dioxide (Fe-TiO2) helps to improve the hardness of the passivation film;

[0069] Adhesion: The adhesion of Example 1 is 10 MPa, and the adhesion of Comparative Example 1 is 8 MPa. The adhesion of Example 1 is stronger, indicating that iron-doped nano-titanium dioxide (Fe-TiO2) helps to improve the adhesion of the passivation film;

[0070] Chemical stability: The chemical stability of Example 1 is 98%, and the chemical stability of Comparative Example 1 is 95%. The chemical stability of Example 1 is better, indicating that the combination of thiosulfate and iron-doped nano-titanium dioxide (Fe-TiO2) helps to improve the chemical stability of the passivation film.

[0071] Example 2

[0072] Specifically, the raw materials of the passivator are as follows: 9 parts of a mixture of urea and inorganic ceramic graphene oxide (GO); 3 parts of a silane coupling agent; 6 parts of iron-doped nano-titanium dioxide Fe-TiO2; 2.8 parts of a mixture of molybdenum disulfide and titanium dioxide; 6.6 parts of polyethylene 2,5-furandicarboxylate; 4.5 parts of thiosulfate; 3.5 parts of a water-soluble derivative of alginic acid; 2.2 parts of hydrogen peroxide; and 4.6 parts of ethanol.

[0073] Comparative Example 2

[0074] Specifically, the raw materials of the passivator are as follows: 9 parts by weight of a mixture of urea and inorganic ceramic graphene oxide (GO); 3 parts by weight of a silane coupling agent; 6 parts by weight of an iron-doped nano-titanium dioxide Fe-TiO2; 2.8 parts by weight of a mixture of molybdenum disulfide and titanium dioxide; 6.6 parts by weight of bio-based PET; 4.5 parts by weight of thiosulfate; 3.5 parts by weight of a water-soluble derivative of alginic acid; 2.2 parts by weight of hydrogen peroxide; and 4.6 parts by weight of ethanol (the polyethylene 2,5-furandicarboxylate in Example 2 is replaced with bio-based PET, and the ethanol is replaced with methanol).

[0075] The passivating agents prepared in Example 2 and Comparative Example 2 were subjected to passivation treatment, and the results are shown in Table 2 below:

[0076] Table 3

[0077]

[0078] From the analysis of Table 3, we can get:

[0079] Appearance of the passivation film: The passivation films of Example 2 and Comparative Example 2 are uniform and have no missing plating, indicating that both formulations can form good passivation films;

[0080] Thickness: The thickness of the passivation film of Example 2 is 1.3 μm, and the thickness of the passivation film of Comparative Example 2 is 1.1 μm. The film thickness of Example 2 is slightly thicker, indicating that the overall mass ratio of the raw materials of Example 2 can provide better protection;

[0081] Corrosion resistance: Example 2 showed better corrosion resistance in the salt spray test, with no obvious corrosion after 1100 hours, while Comparative Example 2 showed slight corrosion after 900 hours, indicating that ethanol can improve the corrosion resistance of the surface of stainless steel parts, while methanol itself is corrosive;

[0082] Hardness: The hardness of Example 2 is 56 HRC, and the hardness of Comparative Example 2 is 52 HRC. The hardness of Example 2 is higher, indicating that polyethylene 2,5-furandicarboxylate (PEF) helps to improve the hardness of the passivation film;

[0083] Adhesion: The adhesion of Example 2 is 11 MPa, and the adhesion of Comparative Example 2 is 9 MPa. The adhesion of Example 2 is stronger, indicating that the combination of ethanol and polyethylene 2,5-furandicarboxylate (PEF) helps to improve the adhesion of the passivation film;

[0084] Chemical stability: The chemical stability of Example 2 is 98.5%, and the chemical stability of Comparative Example 2 is 96%. The chemical stability of Example 2 is better, indicating that adding ethanol to polyethylene 2,5-furandicarboxylate (PEF) helps to improve the chemical stability of the passivation film.

[0085] By comparing the passivating agent formulas of Example 1 with Comparative Example 1 and Example 2 with Comparative Example 2, the comparisons are as follows: Iron-doped nano titanium dioxide (Fe-TiO2) has advantages in improving the corrosion resistance, hardness, adhesion and chemical stability of the passivation film, while polyethylene 2,5-furandicarboxylate (PEF) performs better than bio-based PET in improving the thickness, corrosion resistance, hardness, adhesion and chemical stability of the passivation film, and ethanol performs better than methanol in improving the adhesion and chemical stability of the passivation film.

[0086] The passivators prepared in Example 1-2 and Comparative Example 1-2 were subjected to environmental testing of the wastewater after passivation treatment. The results of the two tests are shown in Table 4 below:

[0087]

[0088]

[0089] Chemical oxygen demand (COD): The COD value of the wastewater treated with the passivator in the embodiment is lower, indicating that less organic pollutants are generated;

[0090] Total nitrogen (TN): The TN value of the wastewater treated with the passivator in the example is lower, indicating that the nitrogen content produced is lower;

[0091] Ammonia nitrogen (NH3-N): The NH3-N value of the wastewater treated with the passivating agent in the embodiment is lower, indicating that the ammonia nitrogen content produced is lower;

[0092] Petroleum: The petroleum value of the wastewater treated with the passivator in the embodiment is lower, indicating that less petroleum pollutants are produced;

[0093] Heavy metals (iron): The heavy metal content in the wastewater treated with the passivating agent in the example is lower, indicating that less heavy metal pollution is generated.

[0094] The results show that the passivator in the embodiment is superior to the passivator in the comparative example in terms of environmental performance, especially in reducing the emission of organic pollutants, nitrogen, ammonia nitrogen, petroleum and heavy metals.

[0095] Example 3

[0096] Electrophoresis passivation treatment using the passivating agent of the present invention

[0097] Specifically, the electrophoresis parameters in the electrophoresis passivation treatment in step 2 are set as follows:

[0098] S2.1, voltage: controlled between 10-20V;

[0099] S2.2, Temperature: maintained between 20-30℃;

[0100] S2.3, Response time: set to 18-28 minutes;

[0101] S2.4, stirring: during the reaction, magnetic stirring is used for continuous stirring, and the stirring speed is controlled at 50-60 rpm.

[0102] Comparative Example 3

[0103] Use the passivating agent of the present invention to carry out conventional passivation treatment

[0104] Specifically, the parameters of the conventional passivation treatment in step 2 are set as follows:

[0105] T2.1, temperature: maintained between 20-30℃;

[0106] T2.2, reaction time: set to 25 to 35 minutes;

[0107] T2.3, Stirring: During the reaction, magnetic stirring is used for uninterrupted stirring, and the stirring speed is controlled at 50-70 rpm.

[0108] After complete passivation treatment, the stainless steel surfaces of Example 3 and Comparative Example 3 are compared, as shown in Table 5 below:

[0109] Table 5

[0110]

[0111] From Table 5 we can get:

[0112] Passivation film thickness: The passivation film formed by electrophoretic passivation treatment is thicker and provides better protection;

[0113] Corrosion resistance: electrophoretic passivation treatment has stronger corrosion resistance and longer salt spray test time;

[0114] Hardness: The hardness of electrophoretic passivation treatment is higher, indicating that the film layer is harder;

[0115] Adhesion: The electrophoretic passivation treatment has stronger adhesion and the film layer is more solid;

[0116] Chemical stability: The electrophoretic passivation treatment has better chemical stability and the film layer is more stable.

[0117] The advantages are: the invention changes the traditional passivating agent formula and introduces iron-doped nano titanium dioxide (Fe-TiO2) to replace undoped nano titanium dioxide, which can improve the corrosion resistance of stainless steel parts while improving their hardness; the combination of polyethylene 2,5-furandicarboxylate (PEF), thiosulfate and ethanol is helpful to further optimize the chemical stability of stainless steel parts; the passivation film formed on the surface of the stainless steel parts has an ideal thickness by adopting electrophoresis technology for passivation treatment, so that the surface has excellent corrosion resistance, high hardness, good adhesion and chemical stability; and the wastewater generated by the passivating agent in the passivation process has less environmental pollution, which is specifically manifested in that the chemical oxygen demand (COD), total phosphorus (TP), total nitrogen (TN), ammonia nitrogen (NH3-N), petroleum and heavy metal contents are all low. Therefore, the passivating agent of the invention is not only efficient and environmentally friendly, but also the treatment method is simple and easy, and is suitable for the surface treatment of stainless steel parts.

[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A chromium-free stainless steel passivator, characterized in that: The raw materials of the passivator are in the following mass parts: 5-10 parts of a mixture of urea and inorganic ceramic graphene oxide; 2-5 parts of a silane coupling agent; 3-7 parts of iron-doped nano-titanium dioxide Fe-TiO2; 2-6 parts of a mixture of molybdenum disulfide and titanium dioxide; 5-10 parts of polyethylene 2,5-furandicarboxylate; 2-5 parts of thiosulfate; 3-8 parts of a water-soluble derivative of alginic acid; 1-3 parts of hydrogen peroxide; and 2-5 parts of ethanol.

2. A chromium-free stainless steel passivator according to claim 1, characterized in that: The composition ratio of the urea and inorganic ceramic graphene oxide mixture is 3:

1.

3. A chromium-free stainless steel passivator according to claim 1, characterized in that: The composition ratio of the molybdenum disulfide and titanium dioxide mixture is 2:

3.

4. The chromium-free stainless steel passivator according to claim 1, characterized in that: The raw materials of the passivator are as follows: 6 parts of a mixture of urea and inorganic ceramic graphene oxide; 5 parts of a silane coupling agent; 4 parts of iron-doped nano-titanium dioxide Fe-TiO2; 5 parts of a mixture of molybdenum disulfide and titanium dioxide; 8 parts of polyethylene 2,5-furandicarboxylate; 4 parts of thiosulfate; 5 parts of a water-soluble derivative of alginic acid; 2.5 parts of hydrogen peroxide; and 4 parts of ethanol.

5. The chromium-free stainless steel passivator according to claim 1, characterized in that: The raw materials of the passivator are as follows: 9 parts of a mixture of urea and inorganic ceramic graphene oxide; 3 parts of a silane coupling agent; 6 parts of iron-doped nano-titanium dioxide Fe-TiO2; 2.8 parts of a mixture of molybdenum disulfide and titanium dioxide; 6.6 parts of polyethylene 2,5-furandicarboxylate; 4.5 parts of thiosulfate; 3.5 parts of a water-soluble derivative of alginic acid; 2.2 parts of hydrogen peroxide; and 4.6 parts of ethanol.

6. A passivation treatment method for chromium-free stainless steel passivator, characterized in that: According to claim 1, the chromium-free stainless steel passivator is passivated, comprising the following passivation steps: Step 1: Preparation: preparation of passivating agent and cleaning of the surface of stainless steel workpiece; Step 2: Electrophoresis passivation treatment: Using electrophoresis technology, the cleaned stainless steel workpiece is used as the cathode, and the graphite electrode is selected as the inert anode. It is placed in an electrophoresis tank filled with a prepared chromium-free stainless steel passivator, and the electrophoresis parameters are set for passivation; Step 3: Post-processing: Take out the passivated stainless steel workpiece, rinse it with deionized water, and put it into a drying oven for drying; Step 4: Quality inspection: Conduct quality inspection on the post-processed stainless steel workpieces. The inspection items include the appearance, thickness, corrosion resistance, hardness, adhesion and chemical stability of the passivation film.

7. The passivation treatment method of a chromium-free stainless steel passivator according to claim 6, characterized in that: The preparation steps of the passivating agent in step 1 are: S1.

1. Prepare raw materials: prepare the mixture of urea and inorganic ceramic graphene oxide, silane coupling agent, iron-doped nano-titanium dioxide Fe-TiO2, mixture of molybdenum disulfide and titanium dioxide, polyethylene 2,5-furandicarboxylate, thiosulfate, water-soluble derivative of alginic acid, hydrogen peroxide and ethanol in the formula weight parts; S1.2, mixing: urea and inorganic ceramic graphene oxide mixture, iron-doped nano titanium dioxide Fe-TiO2, molybdenum disulfide and titanium dioxide mixture, polyethylene 2,5-furandicarboxylate, thiosulfate, water-soluble derivatives of alginic acid are added to the reaction container in sequence, and deionized water of 1 / 3 of the total mass of the above raw materials is added at the same time, and the stirrer is turned on and stirred at a speed of 400-450 rpm for 30 to 40 minutes; S1.3, dissolving: during the stirring process, add the silane coupling agent along the glass rod, and continue stirring for 20 to 30 minutes to form a stable silane coupling agent modified solution; S1.4, adjust pH value: use pH meter to measure pH value of mixed solution. According to the pH value measurement result, when pH value is lower than 6, use plastic dropper to add 5% sodium hydroxide solution drop by drop for neutralization; when pH value is higher than 10, use plastic dropper to add 5% dilute hydrochloric acid drop by drop for adjustment until pH value is stabilized between 6-10; S1.

5. Add hydrogen peroxide and ethanol: under stirring, add hydrogen peroxide and ethanol to the mixed solution with adjusted pH value, and continue stirring for 10 to 15 minutes to complete the preparation of the passivating agent.

8. The passivation treatment method of a chromium-free stainless steel passivator according to claim 6, characterized in that: The cleaning process of the surface of the stainless steel workpiece in step 1 is as follows: the stainless steel workpiece is immersed in a pickling solution composed of nitric acid, sulfuric acid and deionized water in a ratio of 2:1:6 for 15 to 25 minutes.

9. The passivation treatment method of a chromium-free stainless steel passivator according to claim 6, characterized in that: The electrophoresis parameters in the electrophoresis passivation treatment of step 2 are set as follows: S2.1, voltage: controlled between 10-20V; S2.2, Temperature: maintained between 20-30℃; S2.3, reaction time: set to 18-28 minutes; S2.4, stirring: during the reaction, magnetic stirring is used for continuous stirring, and the stirring speed is controlled at 50-60 rpm.

10. The passivation treatment method of a chromium-free stainless steel passivator according to claim 6, characterized in that: The post-processing process in step three is as follows: take out the passivated stainless steel workpiece, rinse it with deionized water for 3-7 times to remove the passivation liquid remaining on the surface, and then put the workpiece into a drying oven for drying at a temperature of 60-80° C. for 45 to 60 minutes.